Clinico-Hemato-Biochemical And Therapeutic Study Of Canine Distemper: A Report From North-Eastern Part Of India - Behera, S.K.; Bordoloi, G.; Behera, P. (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
A study was conducted to evaluate clinico-hemato-biochemical parameters and its therapeutic management in ten dogs with canine distemper virus (CDV) infection. Hematology revealed normocytic hypochromic anemia, thrombocytopenia, neutrophilic leukocytosis and lymphopenia with occasional presence of intracytoplasmic inclusion bodies both in RBC and WBC. Plasma biochemistry revealed mild hypoproteinemia and hyperglobulinemia with marked hypoalbuminemia. Prompt diagnosis followed by aggressive therapy helped the animals to recover completely.